Optimized rice transformation protocol for transformation of the blast susceptible Indica rice accession CO39 - Julian R. Greenwood; Anna N. Glaus (CABI Agriculture and Bioscience)
Abstract Background Many rice transformation protocols have been reported, but optimization is still required to ensure efficient transformation of specific rice accessions. The modified rice transformation protocol presented here builds upon the original protunocol: ‘An improved protocol for efficient transformation and regeneration of diverse Indica rice cultivars’ volume 7, Article number: 49 (2011), Plant Methods. Results Following the aforementioned transformation protocol, calli browning occurred and no Agrobacterium-mediated transformation could be achieved, but this could be remedied by increasing the concentration of l-Proline. Improved callus health lead to successful transformation and proliferation of calli on selection media, but a low frequency of plantlet regeneration occurred when calli were transferred to regeneration media. The efficiency of plantlet regeneration was greatly improved by removing antibiotics from regeneration media, with the presence of escapes selected against during subsequent transfer of plantlets to antibiotic containing rooting media. Transformation of CO39 callus was found to be possible 8 days after callus induction resulting in a time saving of 10 days compared to the original protocol. Conclusions This optimized transformation protocol allows for the generation and survival of healthy CO39 calli, efficient transformation of calli using Agrobacterium, and produces a high frequency of regenerated transgenic plants. These protocol modifications will be useful for optimizing the transformation and regeneration of other recalcitrant Indica rice cultivars, particularly those sensitive to antibiotics during plantlet regeneration.